Foreword - Mensah Danquah, Monica (Ghana Library Journal, 2026)
In 2024, the Department of Information Studies at the University of Ghana organized a landmark international conference under the theme “Fostering Research on Information Behaviour and Digital Literacy in Africa.” The conference provided a unique platform for scholars, practitioners, and policy experts to engage critically with emerging trends, challenges, and opportunities in the evolving information landscape of the continent. Following the success of the conference, the Department formally proposed that selected papers from the event be considered for publication as a special issue of the Ghana Library Journal (GLJ). Upon receiving approval from the Council of the Ghana Library Association, which serves as the publisher of the journal, the editorial process was set in motion.